PERWUJUDAN DARI PERKECUALIAN TERHADAP PRINSIP GENERAL PROHIBITION ON QUANTITATIVE RESTRICTION TERKAIT PENANAMAN MODAL DI INDONESIA - Resa Raytiaputri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract This scientific article discusses Exceptions to the embodiment of one of the principles in the International Trade ie Prohibition of Quantitative Restrictions or better known as the prohibition of quota restrictions, which the authors attributed to investment in Indonesia. Issues raised by the author regarding the reflection of the existence of the rule of fairness exception to the prohibition of the Quantitative Restrictions in the field of investment for Indonesia, which is one of the developing countries. The first discussion of the problems that continue to examine the rules of the embodiment of exceptions to the prohibition of quantitative restrictions contained in legislation or regulation of investment in Indonesia. Where the purpose of this paper to assess and analyze the realization of justice in the fieldof investment related to the rules of the principle of the exception of the prohibition of restriction quantitative for Indonesia as developing countries. This research uses normative research to approach cases and legislation. From the results of the analysis carried out it can be seen that the existence of this exception to the rule it is still not yet fully reflect justice, especially for developing countries like Indonesia, there is still blamed for the developed countries or multinational companies which have the advantage of capital for preferred interests, but all return to business as well as strength a country particularly developing countries to be able to defend the sovereignty of his own country from excessive imports. Awareness of the defeat of the developing countries on technology and the ability of the product markets of developed countries, making the importance of consistent policies and rules of law as one of protection for Indonesia's national interests amid global competition, especially in the field of international trade in capital investment. Considering the capital investment is also needed by Indonesia as one of the efforts to build the country's economy and is closely related to international trade. Key words: fairness, exception, quota, trade, investmentÂ Abstrak Artikel ilmiah ini membahas tentang perwujudan dari Perkecualian Terhadap salah satu prinsip Perdagangan Internasional yaitu Larangan Restriksi Kuantitatif atau yang lebih dikenal dengan larangan pembatasan kuota, dikaitkan dengan penanaman modal di Indonesia. Permasalahan yang diangkat oleh penulis mengenai cerminan keadilan dari keberadaan aturan perkecualian terhadap larangan Restriksi Kuantitatif tersebut dalam bidang penanaman modal bagi Indonesia yang merupakan salah satu negara berkembang. Kemudian dilanjutkan dengan menelaah dari perwujudan aturan perkecualian terhadap larangan restriksi kuantitatif yang terkandung dalam perundang-undangan maupun aturan tentang penanaman modal di Indonesia. Dimana tujuan dari tulisan ini untuk mengkaji dan menganalisis terwujudnya keadilan dalam bidang penanaman modal berkaitan dengan adanya aturan Prinsip Perkecualian terhadap Larangan Restriksi Kuantitatif bagi Indonesia sebagai negara berkembang. Jenis penelitian ialah penelitian normatif dengan metode pendekatan kasus dan perundang-undangan. Dari hasil analisis yang dilakukan maka dapat diketahui bahwa keberadaan aturan perkecualian ini dirasa masih belum sepenuhnya mencerminkan keadilan khususnya bagi negara berkembang seperti Indonesia, masih ada cela bagi negara maju atau perusahaan multinasional yang memiliki keunggulan modal untuk diutamakan kepentingannya, namun semua kembali pada usaha maupun kekuatan suatu negara terutama negara berkembang untuk dapat mempertahankan kedaulatan negaranya sendiri dari impor yang berlebihan. Kesadaran dari kalahnya negara berkembang mengenai teknologi maupun kemampuan pasar produk dari negara maju, menjadikan pentingnya konsistensi kebijakan maupun aturan perundang-undangan sebagai salah satu proteksi bagi kepentingan nasional Indonesia ditengah persaingan global khususnya di bidang perdagangan internasional dalam penanaman modal. Mengingat penanaman modal juga dibutuhkan oleh Indonesia sebagai salah satu upaya membangun perekonomian negara dan erat kaitannya dengan perdagangan internasional. Kata kunci: keadilan, perkecualian, kuota, dagang, modal